Design, Optimization and Characterization of Self-Nanoemulsifying Drug Delivery Systems of Bilastine - Ishraq Kadhim Abbas; Shaimaa Nazar Abd-AlHammid (College of Pharmacy University of Baghdad, 2023)
Self-nanoemulsifying drug delivery systems are innovative methods that have the potential to resolve a variety of drug formulation issues, including solubility, stability and bioavailability. Bilastine is a potent and highly selective H1-antihistamine. The aim of this study is to develop bilastine as an oral self-nanoemulsion to enhance its permeability from prepared formulas and possibility of lymphatic transport. Based on the solubility investigations of bilastine in some oils, surfactants and cosurfactants, fifteen formulae of liquid SNEDDS were created utilizing oleic acid, tween 60 and transcutol as oil, surfactant and co-surfactant respectively. Pseudoternary phase diagrams were used to evaluate the component phase behavior and the area of the nanoemulsion. The prepared formulas were evaluated for particle size, polydispersity index, zetapotential, self-emulsification time, drug content, and robustness to dilution. When compared to the pure drug powder, the produced SMEDDS formulations showed enhanced drug release. This study's findings showed that a formula 8 with a 20% oleic acid, 40% tween 60, and 40% transcutol composition exhibited lower particle size and higher zetapotential with acceptable drug content compared to other formulas and better in-vitro drug release characteristics than pure bilastine powder. All of these criteria favor the development of self-nano emulsifying drug delivery systems as a potential approach to enhance the bioavailability of drugs like bilastine that are poorly soluble. Keywords: Bilastine, SNEDDS